Soil chemical attributes in banana production areas (Musa spp.) (Research, Society and Development, 2021)
He use and management of the soil by different systems lead to changes in the physical and chemical quality of its attributes. The objective of this work was to evaluate the quality of a dystrophic Red Yellow Latosol, based on changes in chemical attributes in different management systems. The experimental design used was a randomized block with a 2x3x2 factorial consisting of three transects in the sloping area (upper, median and lower) and in each transect, two depths for collecting soil samples (0-20 cm and 20-40 cm) with three repetitions. Undisturbed soil samples were collected at random and chemical analysis was carried out. The following were evaluated: pH, sodium (Na+), exchangeable aluminum (Al+3), exchangeable cations (K+, Ca+2 and Mg+2), available phosphorus (P), exchangeable acidity (H++Al+3), matter organic (MO), Sum of bases (SB), Cation Exchange Capacity (CTC) and Aluminum Saturation (m). In the deepest layer of the soil there was an increase in aluminum contents, leading to an increase in saturation by this element, which led to a decrease in base saturation. As for the relief of the experimental area, the lower and median positions have higher values of exchangeable acidity and aluminum saturation. In the upper position, the base sum and base saturation values are higher with less losses and greater increase in organic matter contents due to banana leaves deposited on the surface. The use of multivariate techniques is a very useful tool in analyzing data related to soil chemical attributes.